Cuidado pastoral num centro de tratamento intensivo adulto: referenciais bíblico-teológicos e competências pastorais - Hoepfner, Daniel Annuseck (2012)
This thesis aims to define biblical and theological references in order to extend the pastoral care practical skills in an adult Intensive Care Unit, more precisely in an inpatient unit dedicated to patients in critical health conditions. In this context, human frailty represents a great challenge to theology and, in a particular way, to pastoral theology. Among these theological references, both the theological dimension of the divine solidarity in the midst of the human suffering and the theological dimension of the grace and of the passion revealed in the person of Jesus Christ are emphasized, which underpin both the perspective of the human resistance and of the human submission against the reality of death. Based on the contents achieved, the research aims to map the skills of the pastoral agent when with the patient (and with family members), which will guide the visiting practice in an ecumenical perspective, the establishment of an effective communication, the sensitive and responsible testimony of the Word of God, the use of prayer and religious rituals and of an appropriate interaction with the care team.